Changes in Brain Resting-state Functional Connectivity Associated with Peripheral Nerve Block: A Pilot Study. (August 2016) - Melton, M. Stephen; Browndyke, Jeffrey N.; Harshbarger, Todd B.; Madden, David J.; Nielsen, Karen C.; Klein, Stephen M.
Abstract : Background: Limited information exists on the effects of temporary functional deafferentation (TFD) on brain activity after peripheral nerve block (PNB) in healthy humans. Increasingly, resting-state functional connectivity (RSFC) is being used to study brain activity and organization. The purpose of this study was to test the hypothesis that TFD through PNB will influence changes in RSFC plasticity in central sensorimotor functional brain networks in healthy human participants. Methods: The authors achieved TFD using a supraclavicular PNB model with 10 healthy human participants undergoing functional connectivity magnetic resonance imaging before PNB, during active PNB, and during PNB recovery. RSFC differences among study conditions were determined by multiple-comparison–corrected (false discovery rate–corrected P value less than 0.05) random-effects, between-condition, and seed-to-voxel analyses using the left and right manual motor regions. Results: The results of this pilot study demonstrated disruption of inter hemispheric left-to-right manual motor region RSFC ( e.g., mean Fisher-transformed z [effect size] at pre-PNB 1.05 vs . 0.55 during PNB) but preservation of intra hemispheric RSFC of these regions during PNB. Additionally, there was increased RSFC between the left motor region of interest (PNB-affected area) and bilateral higher order visual cortex regions after clinical PNB resolution ( e.g., Fisher z between left motor region of interest and right and left lingual gyrus regions during PNB, −0.1 and −0.6 vs . 0.22 and 0.18 after PNB resolution, respectively). Conclusions: This pilot study provides evidence that PNB has features consistent with other models of deafferentation, making it a potentially useful approach to investigate brain plasticity. The findings provide insight into RSFC of sensorimotor functional brain networks during PNB and PNB recovery and support modulation of the sensory–motor integration feedback loop as a mechanism for explaining the behavioral correlates of peripherally induced TFD through PNB. Abstract : Using supraclavicular peripheral nerve block (PNB) as a model of temporary functional deafferentation (TFD) in 10 human subjects, functional connectivity magnetic resonance imaging showed disruption of interhemispheric resting-state functional connectivity (RSFC) in the manual motor region but preservation of intrahemispheric RSFC during PNB, with increased RSFC between the affected motor area and bilateral visual cortices upon PNB resolution. TFD produced by PNB produces similar effects on RSFC as other models, which provides a useful model for TFD-induced changes in neuroplasticity.